Environmental, social and governance and the firm life cycle: evidence from the Brazilian market - Moreira, Caritsa Scartaty; Araújo, Jaqueline G. R. de; Silva, Gilson Rodrigues da; Lucena, Wenner Glaucio Lopes (Revista Contabilidade & Finanças, 2023)
The study analyzed the association between environmental, social and governance (ESG) and the life cycle stages of Brazilian publicly-traded companies listed on the B3 S.A. – Brasil, Bolsa, Balcão (B3) from 2010 to 2020. It explores a theoretical gap regarding the relationship between the life cycle stages of companies and ESG initiatives in Brazil, an emerging country. The findings are relevant for understanding how the life cycle stages act as signals of the level of ESG actions of companies and how the market perceives these actions and their ability to create value. The research provides evidence that the fundamentals of the firm life cycle theory function as indicators for several organizational perspectives, including ESG practices. The sample consisted of 109 companies whose data were collected from Thomson Reuters® and analyzed using multiple regression. The model proposed by Dickinson (2011) was used to analyze the life cycle stages. It should be highlighted that the data were also analyzed using the fixed effect as an estimation of the econometric model, but there was a loss of statistical significance in the relationship found, possibly due to the sample selection performed in the unbalanced panel. Based on the sample analyzed and the econometric models used, the results indicate that companies in the birth and turbulence stages have lower levels of ESG practices, particularly in the environmental and social pillars, compared to companies in the maturity stage. The findings also show that ESG initiatives in the Brazilian capital market are associated with measures of companies’ profitability, liquidity, indebtedness, market value, and number of analysts. The research contributes to the analysis of the relationship between the adoption of ESG practices and the life cycle stages of companies in an emerging market, with implications for stakeholders regarding the targeting of resources to sustainable actions.